Transgender debates and healthcare: A critical realist account. (September 2022) - Pilgrim, David
The meta-theoretical resource of critical realism (CR) is deployed in order to examine transgender and healthcare. CR treads a middle way between positivism and postmodernism, within post-Popperian discussions of the philosophy of natural and social science. It focuses on the conditions of possibility for the emergence of a phenomenon under investigation. In this case, the focus is on the emergence of debates about transgenderism in healthcare. These have been technological (about the prospect of biomedical solutions to personal problems) and ideological, with the enlarged salience of identity politics and our currently unresolved "culture wars." Identity politics have brought a focus on epistemological privilege or "lived experience" and on rights to healthcare being driven by consumer choice. The current contestation and its history are discussed in relation to our four planar social being (nature, relationality, socio-economic structures, and our particular personalities) and future scenarios are rehearsed.